Web-Based Library Information System Design - Raden Gilang Komara; Muhammad Rizki Pahlevi; Rivalda Fatah Rachman Hernawan (Universitas Komputer Indonesia, 2023)
Today's libraries need to be combined with technology that can simplify the tasks of librarians who are in charge of managing and serving newcomers. Because the librarian profession is less desirable. The purpose of the design to be designed is to make the librarian profession more attractive to the public. By simplifying the task of a librarian in managing the library, both the recording section and the service to the library. The method used in this study combines conventional methods with existing technology, such as creating a data processing system for outgoing and incoming books, then creating a website so that users can easily get reminders to return books from the library via email or phone number. This system has advantages in terms of book data management which is faster and easier because the data collection uses a system that has been prepared. From the user side, it is also easier to find books, borrow books and return books with the system that has been prepared. The concept of this system is to combine conventional library management systems with existing technology. In the end, this information system can help libraries to facilitate library management. In addition, it can also open and increase public interest in the librarian profession.